Hybrid Deep Learning and FASTBRISK 3D Object Detection Technique for Bin-picking Application - Thanakrit Taweesoontorn; Sarucha Yanyong; Poom Konghuayrob (My University, 2024)
In the field of industrial robotics, robotic arms have been significantly integrated, driven by their precise functionality and operational efficiency.We here propose a hybrid method for binpicking tasks using a collaborative robot, or cobot combining the You Only Look Once version 5 (YOLOv5) convolutional neural network (CNN) model for object detection and pose estimation with traditional feature detection based on the features from accelerated segment test (FAST) technique, feature description using binary robust invariant scalable keypoints (BRISK) algorithms, and matching algorithms.By integrating these algorithms and utilizing a low-cost depth sensor camera for capturing depth and RGB images, the system enhances real-time object detection and pose estimation speed, facilitating accurate object manipulation by the robotic arm.Furthermore, the proposed method is implemented within the robot operating system (ROS) framework to provide a seamless platform for robotic control and integration.We compared our results with those of other methodologies, highlighting the superior object detection accuracy and processing speed of our hybrid approach.This integration of robotic arm, camera, and AI technology contributes to the development of industrial robotics, opening up new possibilities for automating challenging tasks and improving overall operational efficiency.
Keywords: Industrial Vision Systems and Defect Detection